UPAYA GURU BIMBINGAN DAN KONSELING DALAM MENINGKATKAN KETERAMPILAN KOMUNIKASI INTERPERSONAL PESERTA DIDIK DI SMP NEGERI 35 PADANG - Ulfa, Rahmatul - (Bimbingan dan Konseling, 2014)
This research was back ground by student communication who havenât been controlled and there is no well acceptation among student. This research purpose to describe :1) effort of counseling in increasing the interpersonal communication skill of student to teacher at school, 2) the effort of counseling in increasing the interpersonal communication skill of student to their friends.This research is descriptive quantitative research. The research population is all student in high school 35 Padang, they are 452 students. The technique which is used in sample taking is stratified random sampling. The sampling which is taken is 82 students from class VI,VIII, and IX. The instrument which is used in this research is questionnaire, The result of research stated that generally the effort of counseling teacher in increasing the interpersonal communication skill is in good criteria. The result state the sub variable, they are : 1) the effort of counseling in increasing interpersonal communication skill to the teacher is in good criteria, 2) the effort of counseling tincreasing interpersonal communication skill to their friend is in good criteria.